Antibody and DNA sensing pathways converge to activate the inflammasome during primary human macrophage infection. (29th August 2019) - Labzin, Larisa I; Bottermann, Maria; Rodriguez‐Silvestre, Pablo; Foss, Stian; Andersen, Jan Terje; Vaysburd, Marina; Clift, Dean; James, Leo C
Abstract: Inflammasomes are potent innate immune signalling complexes that couple cytokine release with pro‐inflammatory cell death. However, pathogens have evolved strategies to evade this cell autonomous system. Here, we show how antibodies combine with innate sensors in primary human macrophages to detect viral infection and activate the inflammasome. Our data demonstrate that antibody opsonisation of virions can activate macrophages in multiple ways. In the first, antibody binding of adenovirus causes lysosomal damage, activating NLRP3 to drive inflammasome formation and IL‐1β release. Importantly, this mechanism enhances virion capture but not infection and is accompanied by cell death, denying the opportunity for viral replication. Unexpectedly, we also find that antibody‐coated viruses, which successfully escape into the cytosol, trigger a second system of inflammasome activation. These viruses are intercepted by the cytosolic antibody receptor TRIM21 and the DNA sensor cGAS. Together, these sensors stimulate both NLRP3 inflammasome formation and NFκB activation, driving dose‐dependent IL‐1β and TNF secretion, without inducing cell death. Our data highlight the importance of cooperativity between multiple sensing networks to expose viruses to the inflammasome pathway, which is particularly important for how our innate immune system responds to infection in the presence of pre‐existing immunity. Synopsis: Antibodies enhance viral sensing by human macrophages and activate the inflammasome. Viruses routed to the lysosome induce cell death and IL‐1β release, while cytosolic viruses activate the Fc‐receptor TRIM21 and the cGAS/STING‐dependent NLRP3 inflammasome. Antibodies potently activate the inflammasome in primary human macrophages during virus exposure. Virus opsonization enhances virion uptake but not infection, resulting in lysosomal cell death and IL‐1β release. Antibody‐bound viruses that infect the cytosol are detected by TRIM21, leading to capsid degradation and cGAS/STING – dependent NLRP3 inflammasome activation. Abstract : Viral infection promotes NLRP3 inflammasome activation via distinct pathways – one involving lysosomal damage‐mediated cell death, the other via cytosolic antibody receptor TRIM21 and innate immune sensor cGAS.